2002
DOI: 10.1007/s00427-002-0243-2
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of engrailed genes after duplication and speciation events

Abstract: Members of the engrailed class encode transcription factors involved in major steps of metazoan development. Few developmental regulatory genes have been studied in such a wide range of animals. Furthermore duplications of an ancestral engrailed gene independently generated multiple engrailed paralogues in several organisms. This offers the opportunity to reconstruct the evolution of the engrailed family and to study the processes involved in the functional diversification following speciation or duplication e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 148 publications
(132 reference statements)
0
46
0
Order By: Relevance
“…In Drosophila and vertebrates engrailed-like genes have been duplicated during evolution (Gibert, 2002), whereas in the nematode Caenorhabditis elegans only one engrailed-like gene exists (this work). Phenotypic analysis of mutants and mosaic animals revealed that ceh-16/engrailed is required embryonically for the differentiation of the seam cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Drosophila and vertebrates engrailed-like genes have been duplicated during evolution (Gibert, 2002), whereas in the nematode Caenorhabditis elegans only one engrailed-like gene exists (this work). Phenotypic analysis of mutants and mosaic animals revealed that ceh-16/engrailed is required embryonically for the differentiation of the seam cells.…”
Section: Discussionmentioning
confidence: 99%
“…1 in the supplementary material). Besides the homeodomain referred to as Engrailed Homology domain 4 (EH4), CEH-16 possesses at least EH1, EH2 and EH3 [of the five known EH domains (Gibert, 2002)]. EH1 is constituted by the engrailed repressor domain, which binds to Groucho in Drosophila.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It provides a mechanism for evolution of divergent protein functions (Piatigorsky and Wistow 1991;Ohta 1993;Hughes 1994), novel gene expression patterns (Force et al 1999;Lynch and Force 2000), or both (Gibert 2002;Hughes 2002). For example, a single gene that is expressed in different tissues might experience conflicting selective pressures, the result being a compromise between optimal adaptations for any one tissue.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a single gene that is expressed in different tissues might experience conflicting selective pressures, the result being a compromise between optimal adaptations for any one tissue. Duplication of such a locus can lead to specialized patterns of expression among gene copies (Force et al 1999), providing natural selection the freedom to promote tissue-specific functional divergence (e.g., Gibert 2002). The tremendous diversity of extant gene families, taken together with the observation that there is often an acceleration of amino acid substitution rates following gene duplication (Li 1985;Lynch and Conery 2000), suggests that gene duplication has been an important mechanism for functional divergence of genetic systems.…”
Section: Introductionmentioning
confidence: 99%